Implementasi Restorative Justice pada Tindak Pidana Narkotika yang dilakukan oleh Anak - Andrew Reinhard Mathiew Mahulette; Hery Firmansyah (LPPM Universitas Ekasakti Padang, 2023)
The development of an increasingly advanced era has positive and negative impacts on one's environment to grow and develop negatively or positively. Of course, with this development there are negative things that cannot be separated from human social life. A good environment will produce a person's personality to be good, and vice versa if the environment is negative then the person will become negative. A negative environment can lead a person to commit crimes such as narcotics abuse, starting with adults or children. However, currently children can commit criminal acts of drug abuse based on a bad environment. The results of the discussion in this study reveal that a child who falls into drug abuse is the impact of a bad environment, such as a lack of supervision from the family, lack of education, and a bad environment for a child to grow and develop. So that the role of parents is very important in protecting and educating children to avoid drug abuse so there is no need to deal with the law. In addition, the role of the state and government is very important to tackle drug abuse by children, so that a child can still get their rights by providing fair legal considerations and decisions through restorative justice diversion to children.